ifo World Economic Survey May 2019 - Dorine Boumans; Johanna Garnitz (ifo World Economic Survey, 2019)
ifo World Economic Climate:ifo World Economic Climate Recovers Slightly - Advanced Economies: Economic Momentum in Advanced Economies Continues at a Meager Pace - Emerging and Developing Economies: Economic Climate in Emerging Markets and Developing Economies Improves Slightly - Special topic: Changing World Trade Landscape
Keywords: 330